The Correlation Between Level of Diabetic Patients’ Knowledge with Quality of Life in Patients with Type 2 Diabetes Mellitus at Haji Adam Malik Hospital Medan - Rina Amelia (Syiah Kuala University, 2015)
Diabetic complications is usually asssociated with low quality of life in diabetic patients. Knowledge of diabetes become an important role in the management of people with diabetes, at least in self-care to prevent further complication. With a better knowledge about diabetes, people with diabetes will have better self-care in diabetic treatment in order to have better quality of life. This study aimed to evaluate the correlation between the level of diabetic patient’s knowledge and quality of life in patients with type 2 Diabetes Mellitus at Haji Adam Malik Hospital Medan. Ninety subjects were recruited by consecutive sampling technique at outpatients of Endocrinology and Metabolism clinic, Internal Medicine Department Haji Adam Malik Hospital. The level of knowledge about diabetes was assessed by using validated questionnaires, and quality of life was assessed by using the WHOQOL-BREF questionnaire. Pearson correlation was used for statistical analysis. Results showed that majority of patients have a average level of diabetes knowledge (42,2%). Quality of Life was measured by four domains based on the WHOQOL-BREF. The overall quality of life shows that majority of patients have average level quality of life (50%). In the domain of physical health, 65.6% patients have poor level quality of life. Majority of patients have good level quality of life in the domain of psycology (48.9%), social relationships (42.2%) and environment (50%). There was positive correlation between level of knowledge and quality of life (r = 0.239, p0.005). Conclusion This study showed that better knowledge of diabetes could improve quality of life of patients with type 2 diabetes. It is recommended that diabetic patients should improve their understanding about diabetes